Legacy and emerging contaminants in the endangered filter feeder basking shark Cetorhinus maximus. (March 2022) - Boldrocchi, G.; Spanu, D.; Polesello, S.; Valsecchi, S.; Garibaldi, F.; Lanteri, L.; Ferrario, C.; Monticelli, D.; Bettinetti, R.
Abstract: The status of contamination by chemical pollutants on large filter feeding sharks is still largely unknown. This study investigated for the first time the presence of legacy, emerging contaminants and trace elements in multiple tissues of basking sharks. In general, skin showed higher concentration of legacy and emerging contaminants probably due to pollutants being adsorbed onto the dermal denticles of the skin rather than accumulated in the tissue itself. Contaminants measured in both subcutaneous tissue and muscles appeared to strongly correlate with each other, indicating that the former might be a good proxy of muscle contamination in basking sharks. Considering the migratory nature of this species, longevity and feeding ecology, this species represents the perfect candidate to act as early warning bioindicator of regional contamination. In this context, non-lethal subcutaneous biopsies could allow the early detection of any temporal variation in the bioaccumulation of pollutants in the Mediterranean Sea. Highlights: Trace elements, PCBs, DDT and PFAS were quantified in basking sharks. The DDE/DDT ratio suggests that residues derive from old input in the Mediterranean. A predominance of odd-chain length (PFTrDA and PFUnA) was found. Correlations between pollutant levels in subcutaneous tissue and muscles were found. Subcutaneous tissue is a good proxy of muscle levels for PFAS, PCBs and few elements.